Fathu Makkah sebagai awal kejayaan Islam - Syahrullah, Rahmat Makruf (Maliki Interdisciplinary Journal, 2024)
The Treaty of Hudaibiyyah, which was violated by the infidels, made Muslims feel betrayed by them. Betrayed by them. The ceasefire that was previously agreed by both sides was unilaterally violated. Parties, was eventually violated unilaterally. Muslims who consisted of many Tribes united to take over the city of Makkah which was controlled by the pagan Quraysh. They Flocked from the city of Medina to Makkah with the aim of taking over. Take over. The unexpected arrival of the disbelievers of Quraysh made them a little surprised and disbelieving until the Them a little surprised and distrustful until there was almost no resistance from the Quraysh. Quraysh people. Because of this, it became very easy for Muslims to Enter the city of Makkah and then control it. After successfully taking over The city of Makkah the spread of Islam became more widespread, the people of Makkah eventually Could embrace Islam freely, and there was no more rampant ignorance as before. As before. Many recorded in history books about this event. This event also became one of the factors for the success of Islam in the future.